The Influence Of Political Connections And Capital Intensity Ratio On Effective Tax Rate: Moderated by Profitability - Fresti Wulandari, Fanneisa; Lutfi Ardhani (UNIB Press, 2023)
The objective of the research was to determine dan analyze the influence of political connection dan capital intensity ratio on effectivetax rate as a moderating variable on profitability. The research method used is a quantitative method with sampling using purposivesampling. The research sample is 72 mining sector company data listed on the Indonesia Stock Exchange for the 2018-2021 period. The research analysis uses path analysis with the help of the SEM-PLS 3.3 application The results of the study show that political connections affect the effective tax rate. The capital intensity ratio does not affect the effective tax rate. While profitability can moderate political connections and profitability are not able to moderate the capital intensity ratio on the effective tax rate. This research is expected to contribute to providing input dan an overview regarding tax avoidance so that it can help stakeholders such as the government to make decisions dan policies on tax regulations that will be applied.